Composite flame retardant for epoxy resin and preparation method thereof
By surface modification of a mixture of MOF-on-MOF and APP, a composite flame retardant was prepared, which solved the problem of decreased mechanical properties caused by high APP content in epoxy resin and improved both flame retardant and mechanical properties.
Patent Information
- Application Number
- CN202411595806.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Among existing epoxy resin flame retardants, the addition amount of APP is large, which leads to a decrease in the mechanical properties of epoxy resin materials and limited improvement in flame retardant performance.
A composite flame retardant was prepared by surface modification of a mixture of MOF-on-MOF and APP using a phosphorus-containing silane coupling agent. A phosphorus-containing silane coupling agent solution was prepared by mixing DOPO-OH and the silane coupling agent with an aqueous solution of acid, and then mixed with MOF-on-MOF and APP to form a composite flame retardant.
It improves the flame retardant properties of epoxy resin, increases the oxygen index and vertical burning test level, and at the same time improves the mechanical properties of epoxy resin and reduces the loss of mechanical properties.
Smart Images

Figure CN119463298A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flame retardants, in particular to a composite flame retardant that can be used for epoxy resin and a preparation method thereof. Background Art
[0002] Epoxy resin is an important polymer material with excellent mechanical properties, corrosion resistance, and thermal stability. It is widely used in electronic packaging, anti-corrosion coatings, and other fields. However, epoxy resin is flammable and can cause damage to assets and personnel when ignited by open flames. Therefore, it is necessary to add flame retardants to epoxy resin to improve its flame retardancy.
[0003] Phosphorus-containing flame retardants are a commonly used class of flame retardants, boasting advantages such as not producing toxic halogen gases during combustion and exhibiting excellent flame retardancy. Ammonium polyphosphate (APP) is a key phosphorus-containing flame retardant and can be used in a variety of polymer materials, including epoxy resins and polyolefins. However, APP has also exposed several challenges during its use. First, the required dosage of APP is high. For example, when adding APP to epoxy resin, the amount typically needs to exceed 10% to achieve the V0 rating of the UL-94 test. Second, high APP dosages can easily degrade the mechanical properties of the epoxy material. Adding approximately 10% APP to epoxy resin can reduce the impact strength of the resulting epoxy material by approximately 40%. Therefore, while maintaining flame retardancy, reducing the APP dosage and minimizing the mechanical properties of the epoxy resin are key challenges in developing APP-based composite flame retardants.
[0004] Metal-organic framework (MOF) materials are a type of crystalline porous material with a periodic network structure formed by self-assembly of inorganic metal centers and bridging organic ligands. This type of material also has certain flame retardant properties. However, MOF materials have poor flame retardant properties when used alone, and usually require modification of MOF materials or use in combination with other flame retardants to achieve good flame retardant effects. MOF-on-MOF materials are a type of multilayer or hierarchical structured material constructed by depositing one MOF on the surface of another MOF. This structure can provide unique physical and chemical properties, thereby expanding the application range of MOF materials. Compared with MOF materials, MOF-on-MOF materials have enhanced functionality, adjustable surface properties and other characteristics, and can adapt to more application requirements. Therefore, expanding the application of MOF-on-MOF in the field of flame retardancy and developing efficient composite flame retardant systems based on MOF-based materials are current problems that need to be solved in the preparation of high-performance flame retardants using MOF materials. Summary of the Invention
[0005] The purpose of the present invention is to solve the problems of large amount of APP added to epoxy resin and poor mechanical properties of epoxy resin materials in existing flame retardants for epoxy resin, and to provide a composite flame retardant for epoxy resin and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention first provides a method for preparing a composite flame retardant that can be used for epoxy resin, comprising:
[0008] Step 1: Preparation of phosphorus-containing silane coupling agent solution
[0009] Under nitrogen protection, DOPO-OH and a silane coupling agent are added to a reactor for reaction to obtain a phosphorus-containing silane coupling agent, and the phosphorus-containing silane coupling agent is uniformly mixed with an aqueous acid solution to obtain a phosphorus-containing silane coupling agent solution, wherein the silane coupling agent is KH560 or 3-isocyanate propyltrimethoxysilane;
[0010] Step 2: Preparation of MOF-on-MOF materials
[0011] 1) dissolving terephthalic acid and ferric chloride in a solvent and stirring to obtain a mixed solution, then adding the mixed solution into a reactor and heating the reaction to obtain an intermediate product Fe-MOF;
[0012] 2) After the Fe-MOF is dispersed in water, 2-methylimidazole is added to the Fe-MOF aqueous dispersion and stirred, and then an aqueous solution of zinc nitrate is added and stirred to obtain a MOF-on-MOF material;
[0013] Step 3: Preparation of APP and MOF-on-MOF mixture
[0014] mixing APP and MOF-on-MOF to obtain a mixture of APP and MOF-on-MOF;
[0015] Step 4: Preparation of composite flame retardant
[0016] The mixture of APP and MOF-on-MOF obtained in step three is mixed with the phosphorus-containing silane coupling agent solution obtained in step one, and dried to obtain a composite flame retardant.
[0017] Preferably, the reaction temperature in step 1 is 25-140° C., and the reaction time is 3-15 h.
[0018] Preferably, the weight ratio of DOPO-OH to the silane coupling agent in step 1 is 1:(1-1.2).
[0019] Preferably, when the silane coupling agent in step 1 is 3-isocyanatepropyltrimethoxysilane, the solvent 1,4-dioxane is added during the reaction; when the silane coupling agent is KH560, triphenylphosphine is added during the reaction.
[0020] Preferably, the reaction temperature in step 1) is 110° C.-120° C., and the reaction time is 12-24 h.
[0021] Preferably, in step 2, the weight ratio of 2-methylimidazole to zinc nitrate is 82:189, and the weight ratio of the intermediate product Fe-MOF to zinc nitrate is (6-13):1.
[0022] Preferably, the weight ratio of APP to MOF-on-MOF in step 3 is (8-19):1.
[0023] Preferably, the mixing speed in step 4 is 1000-3000 rpm, the mixing temperature is 30-70° C., and the mixing time is 10-30 min.
[0024] Preferably, the weight ratio of the mixture of APP and MOF-on-MOF in step 4 to the phosphorus-containing silane coupling agent solution is (5-10):1.
[0025] The present invention also provides a composite flame retardant that can be used for epoxy resin and is obtained by the above preparation method.
[0026] Beneficial effects of the present invention
[0027] The present invention provides a composite flame retardant that can be used for epoxy resin and a preparation method thereof. The method uses a prepared phosphorus-containing silane coupling agent to modify the surface of a mixture of MOF-on-MOF and APP. When the prepared composite flame retardant is applied to epoxy resin, it exhibits a better flame retardant effect. Under the same addition amount, compared with adding APP alone or a mixture of MOF-on-MOF and APP, the final prepared composite flame retardant has a higher oxygen index and a higher vertical combustion (UL-94) test level, and the prepared epoxy resin has better flame retardant properties. In addition, the composite flame retardant not only improves the flame retardant properties of the epoxy resin, but also effectively improves the mechanical properties of the epoxy resin material compared to using APP alone, solving the problem of excessive reduction in the mechanical properties of the epoxy resin when APP is added to the epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the infrared spectrum of APP and the composite flame retardant 1 prepared in Example 1 of the present invention.
[0029] Figure 2 This is a scanning electron microscope photograph of APP and the composite flame retardant 1 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The present invention first provides a method for preparing a composite flame retardant that can be used for epoxy resin, comprising:
[0031] Step 1: Preparation of phosphorus-containing silane coupling agent solution
[0032] Under nitrogen protection, DOPO-OH and a silane coupling agent are added to a reactor for reaction. The reaction temperature is preferably 25° C.-140° C., and the reaction time is preferably 3-15 hours to obtain a phosphorus-containing silane coupling agent. The phosphorus-containing silane coupling agent is uniformly mixed with an aqueous acid solution to obtain a phosphorus-containing silane coupling agent solution. The weight ratio of water to acid in the aqueous acid solution is preferably (1-3):1, the acid is preferably formic acid or acetic acid, and the weight ratio of the aqueous acid solution to the phosphorus-containing silane coupling agent is preferably (1-2):1. The silane coupling agent is KH560 or 3-isocyanatepropyltrimethoxysilane.
[0033] When the silane coupling agent is 3-isocyanatepropyltrimethoxysilane, a solvent needs to be added during the reaction. The solvent is preferably 1,4-dioxane, and the weight ratio of DOPO-OH, silane coupling agent, and 1,4-dioxane is preferably 1:(1-1.2):(8-12); when the silane coupling agent is KH560, a catalyst triphenylphosphine needs to be added during the reaction. The weight ratio of DOPO-OH, silane coupling agent, and triphenylphosphine is preferably 1:(1-1.2):(0.02-0.2); after the phosphorus-containing silane coupling agent and the acid aqueous solution are evenly mixed, it must be used within 20 minutes and cannot be left for a long time, otherwise the modification effect will be affected.
[0034] Step 2: Preparation of MOF-on-MOF materials
[0035] 1) Dissolve terephthalic acid and ferric chloride in a solvent and stir, the solvent is preferably N,N-dimethylformamide, the weight ratio of terephthalic acid to ferric chloride is preferably 166:162, the stirring temperature is preferably 30°C-50°C, the stirring time is preferably 30-60 minutes, to form a uniform solution, and then transfer the uniform solution to an autoclave for reaction and heating, the reaction temperature is preferably 110°C-120°C, and the reaction time is preferably 12-24 hours. Thereafter, filter and collect the wet intermediate product Fe-MOF, wash and dry the wet intermediate product Fe-MOF to obtain the intermediate product Fe-MOF. The washing and drying is preferably washed three times with methanol, soaked in methanol for 12-24 hours, and then vacuum dried at 80°C-120°C for 12 hours;
[0036] 2) After the intermediate product Fe-MOF obtained in step 1) is dispersed in water, 2-methylimidazole is added to the Fe-MOF aqueous dispersion. After the 2-methylimidazole is dissolved, an aqueous solution of zinc nitrate is added to the Fe-MOF aqueous dispersion under stirring, wherein the stirring time is preferably 4-8 hours, and the wet MOF-on-MOF product is obtained by filtration and separation, and the product MOF-on-MOF material is obtained by post-treatment. The post-treatment is preferably as follows: the collected product is washed with water three times and vacuum dried at 100° C.-120° C. for 6-8 hours. The weight ratio of the 2-methylimidazole to the zinc nitrate is preferably 82:189, and the weight ratio of the intermediate product Fe-MOF to the zinc nitrate is preferably (6-13):1;
[0037] Step 3: Preparation of APP and MOF-on-MOF mixture
[0038] Mixing APP and the MOF-on-MOF prepared in step 2 in a high-speed mixer to obtain a mixture of APP and MOF-on-MOF, wherein the weight ratio of APP to MOF-on-MOF is preferably (8-19):1, and the speed of the high-speed mixer is preferably 1000-3000 revolutions per minute (r / min), and the mixing time is preferably 5-10 minutes;
[0039] Step 4: Preparation of composite flame retardant
[0040] The APP and MOF-on-MOF mixture obtained in step 3 is mixed with the phosphorus-containing silane coupling agent solution obtained in step 1 in a high-speed mixer and dried to obtain a composite flame retardant. The speed in the high-speed mixer is preferably 1000-3000 revolutions per minute (r / min), the mixing temperature is preferably 30°C-70°C, the mixing time is preferably 10-30 minutes, and the drying temperature is preferably 80-100°C, and the drying time is preferably 3-6 hours. The weight ratio of the APP and MOF-on-MOF mixture to the phosphorus-containing silane coupling agent solution is preferably (5-10):1.
[0041] The chemical structures of DOPO-OH, 3-isocyanatepropyltrimethoxysilane and KH560 in the present invention are as follows:
[0042] DOPO-OH:
[0043] KH560:
[0044] 3-Isocyanatepropyltrimethoxysilane:
[0045] The composite flame retardant of the present invention is further described in detail below with reference to the examples, and the raw materials involved in the examples are all commercially available.
[0046] Example 1
[0047] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0048] Under nitrogen, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was complete, the phosphorus-containing silane coupling agent KH560P was obtained.
[0049] (2) Preparation of MOF-on-MOF materials:
[0050] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0051] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0052] (3) Preparation of APP and MOF-on-MOF mixture:
[0053] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0054] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0055] KH560 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0056] (5) Preparation of composite flame retardant:
[0057] The APP and MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 70°C for 10 minutes at a speed of 3000 rpm, with a weight ratio of 9:1. The mixed material was vacuum dried at 100°C for 3 hours to obtain composite flame retardant 1.
[0058] The infrared spectra of the composite flame retardant 1 and APP prepared in Example 1 are as follows: Figure 1 As shown, Figure 1 It can be seen that compared with APP, the prepared composite flame retardant 1 has a wave number of 1597 cm -1 、1201cm -1 、748cm -1 、752cm -1 New infrared peaks appeared in other places.
[0059] Figure 2 The following is a scanning electron microscope photo of the composite flame retardant 1 prepared from APP and Example 1. Figure 2 (a) represents APP, Figure 2 (b) represents composite flame retardant 1, from Figure 2 It can be seen that the surface of APP particles is relatively smooth, while there is a layer of small particles on the surface of composite flame retardant 1.
[0060] In order to illustrate the effect of the composite flame retardant 1 prepared in Example 1 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant 1 prepared in this example and APP were used as flame retardants. The two flame retardants were added to E51 epoxy resin (E51 / DDM) with 4,4'-diaminodiphenylmethane (DDM) as a curing agent at a ratio of 7% by weight of the epoxy resin to prepare a flame-retardant epoxy resin. The flame retardancy and mechanical properties of the materials were tested. The results are shown in Table 1:
[0061] Table 1 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding APP and composite flame retardant 1 to epoxy resin
[0062]
[0063] As shown in Table 1, compared to pure epoxy resin, the epoxy resin material obtained when APP is used alone has a slightly increased oxygen index, reaching the V-1 rating in the UL-94 test, while its impact strength decreases by approximately 50% and its tensile strength decreases by approximately 30%. In contrast, the epoxy resin material using composite flame retardant 1 has an oxygen index close to 30, achieving the V-0 rating in the UL-94 test, with minimal reductions in tensile and impact strength. This demonstrates that composite flame retardant 1 exhibits superior flame retardancy compared to APP. Furthermore, composite flame retardant 1 has a lesser impact on the mechanical properties of the epoxy resin material than APP.
[0064] Comparative Example 1
[0065] (1) Preparation of phosphorus-containing silane coupling agent (KH550P):
[0066] Under nitrogen protection, DOPO-OH, KH550, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was completed, the phosphorus-containing silane coupling agent KH550P was obtained.
[0067] (2) Preparation of MOF-on-MOF materials:
[0068] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0069] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0070] (3) Preparation of APP and MOF-on-MOF mixture:
[0071] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0072] (4) Preparation of phosphorus-containing silane coupling agent KH550P solution:
[0073] KH550 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH550P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0074] (5) Preparation of composite flame retardant:
[0075] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH550P solution were mixed in a high-speed mixer at 3000 rpm and 70°C for 10 minutes. The mixed material was vacuum-dried at 100°C for 3 hours to obtain composite flame retardant D1.
[0076] The chemical structural formula of KH550 in the above comparative example is as follows:
[0077]
[0078] In order to illustrate the effect of the composite flame retardant D1 prepared in Comparative Example 1 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant D1 prepared in this comparative example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 2:
[0079] Table 2 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant D1 to epoxy resin
[0080]
[0081] Comparing Tables 1 and 2, it can be seen that although the epoxy resin material using composite flame retardant D1 has an oxygen index close to 30 and achieves the V-0 level in the UL-94 test, the tensile strength and impact strength of the material are significantly reduced compared to the epoxy resin using composite flame retardant 1. In Example 1 and Comparative Example 1, two different silane coupling agents, KH560 and KH550, were used, respectively, and the effects were significantly different. This shows that composite flame retardant 1 has a better advantage than composite flame retardant D1 in ensuring the mechanical properties of epoxy resin materials, and composite flame retardant 1 has better overall performance.
[0082] Comparative Example 2
[0083] (1) Preparation of MOF-on-MOF materials:
[0084] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0085] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0086] (2) Preparation of APP and MOF-on-MOF mixture:
[0087] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0088] In order to illustrate the effects of the MOF-on-MOF and the mixture of APP and MOF-on-MOF prepared in Comparative Example 2 on the flame retardancy and mechanical properties of epoxy resin, the MOF-on-MOF and the mixture of APP and MOF-on-MOF prepared in this comparative example were added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame-retardant epoxy resin. The flame retardancy and mechanical properties of the materials were tested. The results are shown in Table 3:
[0089] Table 3 Comparison of flame retardancy and mechanical properties of flame retardant materials prepared by adding MOF-on-MOF and a mixture of APP and MOF-on-MOF to epoxy resin
[0090]
[0091] Comparing Tables 1 and 3, it can be seen that the flame retardant and mechanical properties of epoxy resin materials using MOF-on-MOF or a mixture of APP and MOF-on-MOF as flame retardants are lower than those of epoxy resin using composite flame retardant 1. Composite flame retardant 1 has better overall performance.
[0092] Comparative Example 3
[0093] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0094] Under nitrogen protection, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was completed, the phosphorus-containing silane coupling agent KH560P was obtained.
[0095] (2) Preparation of MOF-on-MOF materials:
[0096] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0097] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 5:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0098] (3) Preparation of APP and MOF-on-MOF mixture:
[0099] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0100] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0101] KH560 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0102] (5) Preparation of composite flame retardant:
[0103] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 3000 rpm and 70°C for 10 minutes at a weight ratio of 9:1. The mixture was then vacuum-dried at 100°C for 3 hours to obtain composite flame retardant D3.
[0104] In order to illustrate the effect of the composite flame retardant D3 prepared in Comparative Example 3 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant D3 prepared in this comparative example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 4:
[0105] Table 4 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant D3 to epoxy resin
[0106]
[0107] Comparing Tables 1 and 4, it can be seen that the epoxy resin material using composite flame retardant D3 has an oxygen index of less than 28, achieving the V-1 rating in the UL-94 test. The material's tensile strength and impact strength are not much different from those of the epoxy resin using composite flame retardant 1. In Comparative Example 3, the weight ratio of Fe-MOF to zinc nitrate is 5:1, resulting in a decrease in the flame retardant properties of the epoxy resin material using composite flame retardant D3. This demonstrates that composite flame retardant 1 is superior to composite flame retardant D3 in ensuring the flame retardant properties of epoxy resin materials.
[0108] Comparative Example 4
[0109] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0110] Under nitrogen protection, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was completed, the phosphorus-containing silane coupling agent KH560P was obtained.
[0111] (2) Preparation of MOF-on-MOF materials:
[0112] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0113] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 14:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0114] (3) Preparation of APP and MOF-on-MOF mixture:
[0115] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0116] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0117] KH560 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0118] (5) Preparation of composite flame retardant:
[0119] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 3000 rpm and 70°C for 10 minutes at a weight ratio of 9:1. The mixture was then vacuum-dried at 100°C for 3 hours to obtain composite flame retardant D4.
[0120] In order to illustrate the effect of the composite flame retardant D4 prepared in Comparative Example 4 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant D4 prepared in this comparative example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 5:
[0121] Table 5 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant D4 to epoxy resin
[0122]
[0123] Comparing Tables 1 and 5, it can be seen that the epoxy resin material using composite flame retardant D4 has an oxygen index of less than 28, achieving the V-1 rating in the UL-94 test. The material's tensile strength and impact strength are not much different from those of the epoxy resin using composite flame retardant 1. In Comparative Example 4, the weight ratio of Fe-MOF to zinc nitrate is 14:1, resulting in a decrease in the flame retardant properties of the epoxy resin material using composite flame retardant D4. This demonstrates that composite flame retardant 1 is superior to composite flame retardant D4 in ensuring the flame retardant properties of the epoxy resin material.
[0124] Comparative Example 5
[0125] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0126] Under nitrogen protection, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was completed, the phosphorus-containing silane coupling agent KH560P was obtained.
[0127] (2) Preparation of MOF-on-MOF materials:
[0128] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0129] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0130] (3) Preparation of APP and MOF-on-MOF mixture:
[0131] APP and MOF-on-MOF were mixed in a high-speed mixer at a weight ratio of 7:1 at a rotation speed of 2000 for 10 minutes.
[0132] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0133] KH560 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0134] (5) Preparation of composite flame retardant:
[0135] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 3000 rpm and 70°C for 10 minutes. The mixed material was vacuum-dried at 100°C for 3 hours to obtain composite flame retardant D5.
[0136] In order to illustrate the effect of the composite flame retardant D5 prepared in Comparative Example 5 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant D5 prepared in this comparative example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 6:
[0137] Table 6 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant D5 to epoxy resin
[0138]
[0139] Comparing Tables 1 and 6, we can see that the epoxy resin material using composite flame retardant D5 has an oxygen index of less than 28, achieving a V-1 rating in the UL-94 test. The material's tensile strength and impact strength are similar to those of the epoxy resin using composite flame retardant 1. In Comparative Example 5, the weight ratio of APP to MOF-on-MOF is 7:1, resulting in a decrease in the flame retardancy of the epoxy resin material using composite flame retardant D5. This demonstrates that composite flame retardant 1 is superior to composite flame retardant D5 in ensuring the flame retardancy of epoxy resin materials.
[0140] Comparative Example 6
[0141] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0142] Under nitrogen protection, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was completed, the phosphorus-containing silane coupling agent KH560P was obtained.
[0143] (2) Preparation of MOF-on-MOF materials:
[0144] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0145] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0146] (3) Preparation of APP and MOF-on-MOF mixture:
[0147] APP and MOF-on-MOF were mixed in a high-speed mixer at a weight ratio of 20:1 at a rotation speed of 2000 for 10 minutes.
[0148] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0149] KH560 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0150] (5) Preparation of composite flame retardant:
[0151] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 3000 rpm and 70°C for 10 minutes. The mixed material was vacuum-dried at 100°C for 3 hours to obtain composite flame retardant D6.
[0152] In order to illustrate the effect of the composite flame retardant D6 prepared in Comparative Example 6 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant D6 prepared in this comparative example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 7:
[0153] Table 7 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant D6 to epoxy resin
[0154]
[0155] Comparing Tables 1 and 7, we can see that the epoxy resin material using composite flame retardant D6 has an oxygen index of less than 30, achieving the V-1 rating in the UL-94 test. The material's tensile strength and impact strength are similar to those of the epoxy resin using composite flame retardant 1. In Comparative Example 5, the weight ratio of APP to MOF-on-MOF was 20:1, resulting in a decrease in the flame retardancy of the epoxy resin material using composite flame retardant D5. This demonstrates that composite flame retardant 1 is superior to composite flame retardant D6 in ensuring the flame retardancy of epoxy resin materials.
[0156] Comparative Example 7
[0157] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0158] Under nitrogen protection, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was completed, the phosphorus-containing silane coupling agent KH560P was obtained.
[0159] (2) Preparation of MOF-on-MOF materials:
[0160] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0161] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0162] (3) Preparation of APP and MOF-on-MOF mixture:
[0163] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0164] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0165] KH560 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0166] (5) Preparation of composite flame retardant:
[0167] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 3000 rpm and 70°C for 10 minutes at a weight ratio of 4:1. The mixed material was then vacuum-dried at 100°C for 3 hours to obtain composite flame retardant 1.
[0168] In order to illustrate the effect of the composite flame retardant D7 prepared in Comparative Example 7 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant D7 prepared in this comparative example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 8:
[0169] Table 8 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant D7 to epoxy resin
[0170]
[0171] Comparing Table 1 and Table 8, it can be seen that the epoxy resin material using composite flame retardant D7 has an oxygen index of less than 28, achieving the V-1 level in the UL-94 test. The tensile strength and impact strength of the material are not much different from those of the epoxy resin using composite flame retardant 1. In Comparative Example 7, the weight ratio of the mixture of APP and MOF-on-MOF to the phosphorus-containing silane coupling agent KH560P solution is 4:1, which causes the flame retardant properties of the epoxy resin material using composite flame retardant D7 to decrease. This shows that composite flame retardant 1 is better than composite flame retardant D7 in ensuring the flame retardant properties of epoxy resin materials.
[0172] Comparative Example 8
[0173] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0174] Under nitrogen protection, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.1:0.1 and stirred at 130°C for 6 hours. After the reaction was completed, the phosphorus-containing silane coupling agent KH560P was obtained.
[0175] (2) Preparation of MOF-on-MOF materials:
[0176] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0177] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0178] (3) Preparation of APP and MOF-on-MOF mixture:
[0179] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0180] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0181] KH560 and an aqueous solution of formic acid were uniformly mixed, wherein the weight ratio of water to formic acid was 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P was 1.5:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0182] (5) Preparation of composite flame retardant:
[0183] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 3000 rpm and 70°C for 10 minutes at a weight ratio of 12:1. The mixed material was then vacuum-dried at 100°C for 3 hours to obtain composite flame retardant 1.
[0184] In order to illustrate the effect of the composite flame retardant D8 prepared in Comparative Example 8 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant D8 prepared in this comparative example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 9:
[0185] Table 9 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant D8 to epoxy resin
[0186]
[0187] Comparing Table 1 and Table 9, it can be seen that the oxygen index of the epoxy resin material using composite flame retardant D8 is less than 28, reaching the V-1 level in the UL-94 test. The tensile strength and impact strength of the material are also reduced compared to the epoxy resin using composite flame retardant 1. In Comparative Example 8, the weight ratio of the mixture of APP and MOF-on-MOF to the phosphorus-containing silane coupling agent KH560P solution is 12:1, which causes the flame retardant and mechanical properties of the epoxy resin material using composite flame retardant D8 to decline. This shows that composite flame retardant 1 is better than composite flame retardant D8 in ensuring the flame retardant and mechanical properties of epoxy resin materials.
[0188] Example 2
[0189] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0190] Under nitrogen, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1:0.02 and stirred at 140°C for 15 hours. After the reaction was complete, the phosphorus-containing silane coupling agent KH560P was obtained.
[0191] (2) Preparation of MOF-on-MOF materials:
[0192] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 50°C for 30 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 110°C for 24 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 12 hours, and then vacuum-dried at 120°C for 12 hours to obtain the intermediate Fe-MOF.
[0193] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 6:1. After stirring for 4 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and dried in vacuo at 120°C for 6 hours to obtain the final MOF-on-MOF material.
[0194] (3) Preparation of APP and MOF-on-MOF mixture:
[0195] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 3000 for 5 minutes at a weight ratio of APP to MOF-on-MOF of 8:1.
[0196] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0197] KH560P and an aqueous solution of acetic acid are uniformly mixed, wherein the weight ratio of water to acetic acid is 3:1, and the weight ratio of the aqueous solution of acetic acid to the phosphorus-containing silane coupling agent KH560P is 2:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0198] (5) Preparation of composite flame retardant:
[0199] The APP and MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 30°C for 30 minutes at a speed of 3000 rpm, with a weight ratio of 5:1. The mixed material was vacuum-dried at 100°C for 3 hours to obtain composite flame retardant 2.
[0200] In order to illustrate the effect of the composite flame retardant 2 prepared in Example 2 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant 2 prepared in this example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 10:
[0201] Table 10 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant 2 to epoxy resin
[0202]
[0203] Comparing Tables 1 and 10, we can see that the epoxy resin material using composite flame retardant 2 has an oxygen index greater than 30, achieving a V-0 rating in the UL-94 test. The material's tensile strength and impact strength are significantly improved compared to the epoxy resin using APP. This demonstrates that composite flame retardant 2 demonstrates superior performance compared to APP in improving the flame retardancy and mechanical properties of epoxy resin materials.
[0204] Example 3
[0205] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0206] Under nitrogen, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1:0.2 and stirred at 60°C for 15 hours. After the reaction was complete, the phosphorus-containing silane coupling agent KH560P was obtained.
[0207] (2) Preparation of MOF-on-MOF materials:
[0208] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 120°C for 12 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 24 hours, and then vacuum-dried at 80°C for 12 hours to obtain the intermediate Fe-MOF.
[0209] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 13:1. After stirring for 8 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and dried in vacuo at 100°C for 8 hours to obtain the final MOF-on-MOF material.
[0210] (3) Preparation of APP and MOF-on-MOF mixture:
[0211] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 1000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 19:1.
[0212] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0213] KH560P and an aqueous solution of formic acid are uniformly mixed, wherein the weight ratio of water to formic acid is 1:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P is 1:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0214] (5) Preparation of composite flame retardant:
[0215] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 70°C for 10 minutes at a speed of 1000 rpm, with a weight ratio of 10:1. The mixed material was vacuum-dried at 80°C for 6 hours to obtain composite flame retardant 3.
[0216] In order to illustrate the effect of the composite flame retardant 3 prepared in Example 3 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant 3 prepared in this example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame-retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 11:
[0217] Table 11 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant 3 to epoxy resin
[0218]
[0219] Comparing Table 1 and Table 11, we can see that the epoxy resin material using composite flame retardant 3 has an oxygen index of 29.6, achieving the V-0 rating in the UL-94 test. The material's tensile strength and impact strength are significantly improved compared to the epoxy resin using APP. This demonstrates that composite flame retardant 3 demonstrates superior performance compared to APP in improving the flame retardancy and mechanical properties of epoxy resin materials.
[0220] Example 4
[0221] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0222] Under nitrogen, DOPO-OH, KH560, and triphenylphosphine were added to a reactor in a weight ratio of 1:1.2:0.2 and stirred at 60°C for 15 hours. After completion of the reaction, the phosphorus-containing silane coupling agent KH560P was obtained.
[0223] (2) Preparation of MOF-on-MOF materials:
[0224] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 120°C for 12 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 24 hours, and then vacuum-dried at 80°C for 12 hours to obtain the intermediate Fe-MOF.
[0225] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous zinc nitrate solution was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 11:1. After stirring for 8 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and dried in vacuo at 100°C for 8 hours to obtain the final MOF-on-MOF material.
[0226] (3) Preparation of APP and MOF-on-MOF mixture:
[0227] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 12:1.
[0228] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0229] KH560P and an aqueous solution of formic acid are uniformly mixed, wherein the weight ratio of water to formic acid is 1:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent KH560P is 1:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0230] (5) Preparation of composite flame retardant:
[0231] The APP and MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 2000 rpm and 60°C for 20 minutes, with a weight ratio of 6:1. The mixed material was vacuum-dried at 80°C for 6 hours to obtain composite flame retardant 4.
[0232] In order to illustrate the effect of the composite flame retardant 4 prepared in Example 4 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant 4 prepared in this example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 12:
[0233] Table 12 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant 4 to epoxy resin
[0234]
[0235] Comparing Tables 1 and 11, we can see that the epoxy resin material using composite flame retardant 4 has an oxygen index of 31.1, achieving the V-0 rating in the UL-94 test. The material's tensile strength and impact strength are significantly improved compared to the epoxy resin using APP. This demonstrates that composite flame retardant 4 demonstrates superior performance compared to APP in improving the flame retardancy and mechanical properties of epoxy resin materials.
[0236] Example 5
[0237] (1) Preparation of phosphorus-containing silane coupling agent (KH560P):
[0238] Under nitrogen, DOPO-OH, KH560, and triphenylphosphine were added to a reactor at a weight ratio of 1:1.1:0.15 and stirred at 60°C for 15 hours. After completion of the reaction, the phosphorus-containing silane coupling agent KH560P was obtained.
[0239] (2) Preparation of MOF-on-MOF materials:
[0240] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 120°C for 12 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 24 hours, and then vacuum-dried at 80°C for 12 hours to obtain the intermediate Fe-MOF.
[0241] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous zinc nitrate solution was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 9:1. After stirring for 8 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and dried in vacuo at 100°C for 8 hours to obtain the final MOF-on-MOF material.
[0242] (3) Preparation of APP and MOF-on-MOF mixture:
[0243] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 3000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 11:1.
[0244] (4) Preparation of phosphorus-containing silane coupling agent KH560P solution:
[0245] KH560P and an aqueous solution of acetic acid are uniformly mixed, wherein the weight ratio of water to acetic acid is 3:1, and the weight ratio of the aqueous solution of acetic acid to the phosphorus-containing silane coupling agent KH560P is 1:1, to obtain a phosphorus-containing silane coupling agent KH560P solution.
[0246] (5) Preparation of composite flame retardant:
[0247] The APP / MOF-on-MOF mixture and the phosphorus-containing silane coupling agent KH560P solution were mixed in a high-speed mixer at 3000 rpm and 60°C for 20 minutes, with a weight ratio of 8:1. The mixed material was vacuum-dried at 100°C for 3 hours to obtain composite flame retardant 5.
[0248] In order to illustrate the effect of the composite flame retardant 5 prepared in Example 5 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant 5 prepared in this example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame-retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 13:
[0249] Table 13 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant 5 to epoxy resin
[0250]
[0251] Comparing Table 1 and Table 13, we can see that the epoxy resin material using composite flame retardant 5 has an oxygen index of 30.4, achieving the V-0 rating in the UL-94 test. The material's tensile strength and impact strength are significantly improved compared to the epoxy resin using APP. This demonstrates that composite flame retardant 5 demonstrates superior performance compared to APP in improving the flame retardancy and mechanical properties of epoxy resin materials.
[0252] Example 6
[0253] (1) Preparation of phosphorus-containing silane coupling agent:
[0254] Under nitrogen protection, DOPO-OH, 3-isocyanatepropyltrimethoxysilane, and 1,4-dioxane were added to a reactor in a weight ratio of 1:1.1:10 and stirred at 40°C for 6 hours. After the reaction was completed, a phosphorus-containing silane coupling agent was obtained.
[0255] (2) Preparation of MOF-on-MOF materials:
[0256] Terephthalic acid and ferric chloride were added to N,N-dimethylformamide in a weight ratio of 166:162 and stirred at 30°C for 60 minutes to form a homogeneous solution. The homogeneous solution was then transferred to an autoclave and heated at 115°C for 20 hours. The wet intermediate Fe-MOF was then collected by filtration. The wet intermediate Fe-MOF was washed three times with methanol, soaked in methanol for 20 hours, and then dried in a vacuum oven at 100°C for 12 hours to obtain the intermediate Fe-MOF.
[0257] After dispersing the Fe-MOF in water, 2-methylimidazole was added to the aqueous Fe-MOF dispersion. Once the 2-methylimidazole dissolved, an aqueous solution of zinc nitrate was added to the Fe-MOF dispersion while stirring. The weight ratio of 2-methylimidazole to zinc nitrate was controlled to be 82:189, and the weight ratio of Fe-MOF to zinc nitrate was 10:1. After stirring for 6 hours, the wet MOF-on-MOF product was separated by filtration. The collected product was washed three times with water and vacuum-dried at 110°C for 7 hours to obtain the final MOF-on-MOF material.
[0258] (3) Preparation of APP and MOF-on-MOF mixture:
[0259] APP and MOF-on-MOF were mixed in a high-speed mixer at a rotation speed of 2000 for 10 minutes at a weight ratio of APP to MOF-on-MOF of 9:1.
[0260] (4) Preparation of phosphorus-containing silane coupling agent solution:
[0261] The phosphorus-containing silane coupling agent prepared in step (1) is uniformly mixed with an aqueous solution of formic acid, wherein the weight ratio of water to formic acid is 2:1, and the weight ratio of the aqueous solution of formic acid to the phosphorus-containing silane coupling agent is 1.5:1, to obtain a phosphorus-containing silane coupling agent solution.
[0262] (5) Preparation of composite flame retardant:
[0263] The APP and MOF-on-MOF mixture and the phosphorus-containing silane coupling agent solution were mixed in a high-speed mixer at 70°C for 10 minutes at a speed of 3000 rpm, with a weight ratio of 9:1. The mixed material was vacuum-dried at 100°C for 3 hours to obtain composite flame retardant 6.
[0264] In order to illustrate the effect of the composite flame retardant 6 prepared in Example 6 on the flame retardancy and mechanical properties of epoxy resin, the composite flame retardant 6 prepared in this example was added to E51 / DDM at a ratio of 7% by weight of the epoxy resin to prepare a flame-retardant epoxy resin. The flame retardancy and mechanical properties of the material were tested. The results are shown in Table 14 below:
[0265] Table 14 Comparison of flame retardant and mechanical properties of flame retardant materials prepared by adding composite flame retardant 6 to epoxy resin
[0266]
[0267]
[0268] Comparing Table 1 and Table 14, we can see that the epoxy resin material using composite flame retardant 6 has an oxygen index of 30.9, achieving the V-0 rating in the UL-94 test. The material's tensile strength and impact strength are significantly improved compared to the epoxy resin using APP. This demonstrates that composite flame retardant 6 demonstrates superior performance compared to APP in improving the flame retardancy and mechanical properties of epoxy resin materials.
Claims
1. A method for preparing a composite flame retardant that can be used for epoxy resin, characterized in that: include: Step 1: Preparation of phosphorus-containing silane coupling agent solution Under nitrogen protection conditions, DOPO-OH and a silane coupling agent are added to a reactor for reaction to obtain a phosphorus-containing silane coupling agent, and the phosphorus-containing silane coupling agent is uniformly mixed with an aqueous acid solution to obtain a phosphorus-containing silane coupling agent solution, wherein the silane coupling agent is KH560 or 3-isocyanate propyltrimethoxysilane; Step 2: Preparation of MOF-on-MOF materials 1) dissolving terephthalic acid and ferric chloride in a solvent and stirring to obtain a mixed solution, then adding the mixed solution into a reactor and heating the reaction to obtain an intermediate product Fe-MOF; 2) After Fe-MOF is dispersed in water, 2-methylimidazole is added to the Fe-MOF aqueous dispersion and stirred, and then an aqueous solution of zinc nitrate is added and stirred to obtain a MOF-on-MOF material; Step 3: Preparation of APP and MOF-on-MOF mixture mixing APP and MOF-on-MOF to obtain a mixture of APP and MOF-on-MOF; Step 4: Preparation of composite flame retardant The mixture of APP and MOF-on-MOF obtained in step three is mixed with the phosphorus-containing silane coupling agent solution obtained in step one, and dried to obtain a composite flame retardant.
2. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: The reaction temperature in step 1 is 25-140° C., and the reaction time is 3-15 h.
3. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: The weight ratio of DOPO-OH and silane coupling agent in step 1 is 1:(1-1.2).
4. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: When the silane coupling agent in step 1 is 3-isocyanatepropyltrimethoxysilane, the solvent 1,4-dioxane is added during the reaction; when the silane coupling agent is KH560, triphenylphosphine is added during the reaction.
5. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: The reaction temperature of step 1) in step 2 is 110°C-120°C, and the reaction time is 12-24h.
6. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: In step 2, the weight ratio of 2-methylimidazole to zinc nitrate is 82:189, and the weight ratio of the intermediate product Fe-MOF to zinc nitrate is (6-13):
1.
7. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: The weight ratio of APP and MOF-on-MOF described in step 3 is (8-19):
1.
8. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: The mixing speed in step 4 is 1000-3000 rpm, the mixing temperature is 30-70° C., and the mixing time is 10-30 min.
9. The method for preparing a composite flame retardant for epoxy resin according to claim 1, characterized in that: The weight ratio of the mixture of APP and MOF-on-MOF described in step 4 to the phosphorus-containing silane coupling agent solution is (5-10):
1.
10. The composite flame retardant for epoxy resin obtained by the preparation method according to claim 1.
Citation Information
Patent Citations
Silane coupling agent containing DOPO group and preparation method thereof
CN101792537A
Flame-retardant resin composition, thermosetting resin composition, flame-retardant engineering plastic and composite metal substrate
CN107641290A
DOPO-LDH composite flame retardant and preparation method thereof, and halogen-free flame-retardant EPDM ethylene propylene diene monomer material and applications thereof
CN108623844A
Preparation method of compound flame retardant prepared from brucite and used for epoxy resin
CN115322439A
Antistatic flame-retardant rubber conveying belt and preparation method thereof
CN116160710A
Cited By
Composite flame retardant, epoxy resin composite material and preparation method thereof
CN122145874A